A macroeconomic vulnerability model for the euro area - David Sondermann; Nico Zorell (European Central Bank (ECB), 2019)
Macroeconomic imbalances increase the vulnerability of an economy to adverse shocks, which in turn can lead to crises with severe economic and social costs. We propose an early warning model that predicts such crises. We identify a set of macroeconomic indicators capturing domestic and external imbalances that jointly predict severe recessions (i.e. growth crises) in a multivariate discrete choice framework. The approach allows us to quantify an economy's macroeconomic vulnerabilities at any point in time. In particular, the model would have pointed early on to emerging vulnerabilities in all the euro area countries that registered severe recessions in the years after 2007. We also show that the model can be applied beyond the euro area crisis in that its main results remain robust to changes in assumptions and sample composition.
Keywords: E37; E44; F47; O52; 330; macroeconomic imbalances; early warning models; growth crises